Just mercy : a story of justice and redemption - Stevenson, Bryan (One World, an imprint of Random House, 2024)
"Bryan Stevenson was a young lawyer when he founded the Equal Justice Initiative, a legal practice dedicated to defending those most desperate and in need: the poor, the wrongly condemned, and women and children trapped in the farthest reaches of our criminal justice system. One of his first cases was that of Walter McMillian, a young man who was sentenced to die for a notorious murder he insisted he didn't commit. The case drew Bryan into a tangle of conspiracy, political machination, and legal brinksmanship--and transformed his understanding of mercy and justice forever. Just Mercy is at once an unforgettable account of an idealistic, gifted young lawyer's coming of age, a moving window into the lives of those he has defended, and an inspiring argument for compassion in the pursuit of true justice"--Amazon.com.